2022
DOI: 10.1002/marc.202200176
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Adhesive Hyaluronic Acid/Antimicrobial Peptide Composite Hydrogel with Antioxidant Capability and Photothermal Activity for Infected Wound Healing

Abstract: Bacterial infection can delay wound healing, causing wounds to deteriorate and even threaten the patient's life. Recently, although many composite hydrogels as wound dressing have been developed, it is still highly desired to construct photothermal hydrogels with antimicrobial and antioxidant properties to accelerate the infected wound healing. In this work, a hyaluronic acid (HA)‐based composite hydrogel consisting of a dopamine‐substituted antimicrobial peptide (DAP) and Iron (III) ions is developed, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The results of this research are useful for the development of the inherent antibacterial hydrogels based on the heterochiral peptides. Xiong et al reported a hyaluronic acid (HA)-hydrogel containing Fe 3+ ions and a dopamine-modified antimicrobial peptide (DAP), possessing photothermal-assisted wound-healing characteristics for bacterial infection [ 111 ]. The inherent antimicrobial DAP peptide acts as an ROS-scavenger and can reinforce the hydrogel structure by forming Schiff’s base and coordination bonds with aldehyde hyaluronic acid (AHA) and Fe 3+ , respectively.…”
Section: Biomedical Applications Of Peptide-based Hydrogelsmentioning
confidence: 99%
“…The results of this research are useful for the development of the inherent antibacterial hydrogels based on the heterochiral peptides. Xiong et al reported a hyaluronic acid (HA)-hydrogel containing Fe 3+ ions and a dopamine-modified antimicrobial peptide (DAP), possessing photothermal-assisted wound-healing characteristics for bacterial infection [ 111 ]. The inherent antimicrobial DAP peptide acts as an ROS-scavenger and can reinforce the hydrogel structure by forming Schiff’s base and coordination bonds with aldehyde hyaluronic acid (AHA) and Fe 3+ , respectively.…”
Section: Biomedical Applications Of Peptide-based Hydrogelsmentioning
confidence: 99%
“…[172][173][174] Xie et al introduced lignincopper sulfide (LS-CuS) nanocomposites into PVA networks to prepare LS-CuS@PVA composite hydrogels for multimodal combined antibacterial activity. Under NIR light irradiation, the local heat generated by the LS-CuS@PVA composite [159] Copyright 2022, WILEY-VCH.…”
Section: Ptt-multimodal Therapymentioning
confidence: 99%
“…In addition, DAP also has a ROS scavenging function, which can effectively regulate the oxidative stress of the wound site and reduce the occurrence of adverse reactions such as inflammation ( Figure 13 ). [ 159 ] In addition to combining with the traditional hydrogel matrix, the polypeptide can also self‐assemble to form a hydrogel under the stimulation of the external environment. Wang and co‐workers incorporated the PTA cypate into a hydrogel formed by the self‐assembly of an octapeptide (IKFQFHFD) under neutral conditions, realizing the controlled release of the peptide under acidic conditions and combined photothermal disinfection.…”
Section: Photothermal Hydrogels For Infected Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…While intrinsically antibacterial materials help to combat antibiotic resistance, , traditional small molecule antibiotics are better able to reach all possible contamination. To prevent bacterial growth in wound dressings, HA-based hydrogels have utilized antimicrobial peptides, silver nanoparticles, and aminoglycosides. , To this end, antibacterial activity has been imparted into HA-based hydrogels through either ionic or covalent attachment of the antibiotic to the HA hydrogel. Ionic incorporation of an antibiotic into a hydrogel is simple and typically results in a burst release of the antibiotic. , Conversely, covalent incorporation of the antibiotic typically results in a slow release of antibiotic from the hydrogel or sustained antibacterial activity at the surface. , Combining the short time scale of ionic release and the longer time scale of covalent release can provide an additional layer of control over the delivery profile of the gel.…”
Section: Introductionmentioning
confidence: 99%